Pendidikan kesehatan berpengaruh terhadap pengetahuan santri tentang Scabies - Setyorini, Andri; Lutfiah, Rahmiati; Hartiningsih, Sri Nur (Health Sciences and Pharmacy Journal, 2022)
Scabies is a skin disease with a high incidence and prevalence worldwide, especially in tropical and subtropical climates. Islamic boarding school is a place that can facilitate the emergence of various skin diseases, one of which is scabies which can be caused by bad habits. Knowledge certainly has a role to play in prevention by practicing good personal hygiene. Providing health education can be used to improve health status. This study aims to determine the effect of health education on scabies on the level of knowledge of students at the Al I'tishom Islamic boarding school Gunung Kidul Yogyakarta. This research is a pre-experimental research with one group pre-post-test design. The population in this study were students aged 11-15 years at the Al I'tishom Islamic boarding school in Gunung Kidul Yogyakarta. The sample in this study amounted to 34 respondents who were determined using the Issac and Michael formula and the sample was taken using a simple random sampling technique. This study used the Wilcoxon Signed Rank Test. The result of this study is the level of knowledge students about scabies at the Al I'tishom Islamic boarding school Gunung Kidul Yogyakarta before health education about scabies was carried out was the majority in the sufficient category, namely as many as 28 respondents (80%), the level of knowledge of students about scabies at the Al I'tishom Islamic boarding school Gunung Kidul Yogyakarta after The majority of health education on scabies was conducted in the good category, namely 23 respondents (65.71%). The conclusion in this study was that there is an effect of Health education on scabies on the level of knowledge of students at Al I'tishom Islamic boarding school Gunung Kidul Yogyakarta.